Rare brown tumour of the mandible secondary to tertiary hyperparathyroidism in a renal transplant recipient. Issue 9 (24th September 2019) - Guéroult, Aurélien M; Cameron, Malcolm
Abstract : Brown tumours are rare osteolytic lesions that occur secondary to hyperparathyroidism (HPT). In 2% of all cases, the craniofacial bones are affected, most frequently the mandible. HPT is classified according to aetiology into three types, of which tertiary HPT is the rarest. Here we present the case of a 42-year-old man who had received a renal transplant 16 years previously and was referred due to swelling on the right side of his jaw. An orthopantomogram revealed a multilocular radiolucency in the right body of the mandible. The bony lesion was treated by surgical enucleation. After histopathological examination of the lesion, the diagnosis of brown tumour of the mandible secondary to tertiary HPT was reached. The patient's recovery was uneventful and follow-up radiography showed good bone healing.